Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China - Liu, Sheng-Nan; Tang, Liang (Zootaxa, 2017)
Seven new species of the Stenus cirrus group collected from Guangxi, South China are described and illustrated: S. hujiayaoi Liu and Tang, sp. n., S. bullatus Liu and Tang, sp. n., S. exesus Liu and Tang, sp. n., S. damingshanus Liu and Tang, sp. n., S. jinxiuensis Liu and Tang, sp. n., S. lianhuashanus Liu and Tang, sp. n., S. hechiensis Liu and Tang, sp. n. The diagnostic characters of the new species are illustrated, and a key to species of the group from Guangxi is provided.